Macrophage phenotype after human refluxate exposure, esophageal dysmotility and their correlation with gastroesophageal reflux disease - A. V. Paraskevova; A. S. Trukhmanov; O. A. Storonova; S. V. Lyamina; S. V. Kalish; S. S. Pirogov; A. B. Ponomarev; D. E. Rumyantseva; I. Yu. Malyshev; I. V. Maev; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of the study. To investigate the esophageal dysmotility, changes in the esophageal mucosa and the immune response depending on the type of refluxate in gastroesophageal reflux disease (GERD) patients.Material and methods. 68 patients with GERD were recruited: 28 (14 men; mean age, 45.74 ± 2.23 years) nonerosive reflux disease (NERD), 22 (15 men; mean age, 45.0 ± 3.24 years) erosive reflux disease (EE), 18 (13 men; mean age, 47.22 ± 2.95) Barrett’s Esophagus (BE). GERD patients underwent esophageal high-resolution manometry (HRM) with a 22-channel water-perfused catheter and Solar GI system (Medical Measurements Systems, Enschede, the Netherlands), 24-hour impedance and pH monitoring using the Ohmega Ambulatory Impedance pH Recorder (Medical Measurements Systems). We analyzed receptor characteristics of monocyte-derived macrophages in all groups of patients.Results. On HRM examination, we showed that DCI (distal contractile integral) in NERD patients was higher than in EE (p = 0.088) and BE (p = 0.076), also LES RP (lower esophageal sphincter resting pressure) in NERD patients was higher than in EE (p = 0.039) and BE (p = 0.012). The analysis of reflux characteristics showed that the total reflux time with pH < 4 for BE patients was longer than that for NERD and EE patients. An analysis of receptor characteristics of monocyte-derived macrophages showed the prevalence of CD25 and CD80 expression in all groups of patients.Conclusion. An analysis of the phenotype of macrophages derived from blood monocytes of GERD patients revealed a prevalence of М1 macrophages that was typical for the Th1 type of immune response. The degree of esophageal dysmotility was correlated with GERD severity and type.